Pelatihan Public Speaking untuk Meningkatkan Kepercayaan Diri Siswa SMAN 1 Bebandem - Ni Luh Putu Ning Septyarini Putri Astawa; Putu Anna Widyawati; Ni Putu Yowi Lestari; Kadek Intan Janeta Pratiwi; I Putu Candra Suhendra; Ni Gusti Ayu Nuansih Dewi (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2021)
Public speaking skills is the skills that persue people to design words and beautiful sentences which is able to attract people's attention. Therefore, the purpose of this activity is to increase the knowledge of students at SMAN 1 Bebandem in public speaking. This activity focuses on providing socialization about the importance of understanding and implementing public speaking to increase self-confidence, improve self- quality, and be able to think critically. The methods used in this activity are lecture, simulation, and practice methods. The participants were actively involved in this activity, seen from the enthusiasm they had during the practice. Significant changes in students' confidence in public speaking could be seen in the pre-test results and the post-test data. In addition, the significant changes could be seen from the enthusiasm of the participants in the activity by asking and discussing.